Analisis Strategi Produk Dalam Meningkatkan Penjualan Krupuk Sanjai Jaso Mandeh Aur Kuning Kota Bukittinggi Dalam Perspektif Manajemen Bisnis Syariah - Alami, Alda Arta; Yenti, Endri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The background for the author to discuss this is because of the decline in sales levels in 2020-2023, which was caused by the lack of product innovation in Sanjai Jaso Mandeh crackers, limited flavor variants and unattractive packaging designs, and high competition with similar businesses. As one of the traditional Minang snack products, Sanjai Jaso Mandeh crackers have great potential to be of interest to tourists as a typical Minangkabau souvenir. Therefore, the purpose of the researcher in conducting this research is to find out what kind of product strategy can be applied to increase sales in the Sanjai Jaso Mandeh cracker business in increasing sales in its business from a sharia business management perspective. The type of research that the author uses is field research using qualitative research methods, the data collection techniques that the author uses are through interviews, observation and documentation, the data analysis techniques used are SWOT analysis, internal factor evaluation (IFE) matrix analysis, SWOT matrix, and Score weighting. The results of the research conducted in the field can be concluded that the owner must increase product variations and improve the packaging design that is less attractive, in addition, the stage of the function of sharia business management, especially strategic planning, also needs to be maximized so that the main strengths of the Sanjai Jaso Mandeh cracker product such as its distinctive taste and strategic location can be utilized optimally to increase sales of Sanjai Jaso Mandeh crackers.